Trends of Mismatches in Real-Time RT-PCR Assays Developed by the National Institute of Infectious Diseases, Japan for Omicron Variant of Severe Acute Respiratory Syndrome Coronavirus 2 - Shirato, Kazuya; Ujike, Makoto; Kawase, Miyuki (Japanese Journal of Infectious Diseases, 2023)
The Omicron variant of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) emerged in late 2021 and gradually overtook the Delta variant, which was the predominant variant at that time. The Omicron variant has been consecutively replaced by related sublineages. The real-time RT-PCR assays developed by the National Institute of Infectious Diseases (NIID), Japan (i.e., the NIID-N2 and NIID-S2 assays) are the reference assays that have been used in Japan since the outbreak of SARS-CoV-2. To evaluate the applicability of the NIID assays for the Omicron variants, trends in the prevalence of nucleotide mismatches in the primer/probe sequences were traced using sequences registered in the Global Initiative on Sharing Avian Influenza Data database. Approximately 99% of the deposited Omicron variant sequences did not have any mismatches in the NIID assay primer/probes from January to August 2022. This indicates that the NIID assays have been able to detect the changing SARS-CoV-2 Omicron variants.